Rise & Fall of Long-Term Capital - LOWENSTEIN, ROGER; Mohan, Padam Shree Chandra (Gyan Management Journal, 2022)
Fascinating story of the basic human instinct of gambling & get rich quick. Equally responsible is the infinite spiral which a run of serial victories creates of invincibility in people. Kings, soldiers, entrepreneurs, business leaders, sportsmen, and for that matter every individual has fallen a prey to this 'Lucky stars' gambit. Crony sycophants add further fuel. Unfortunately, luck runs out one day. Result is sheer murder. Millions bet daily in the casinos of Las Vegas, Macao & Kathmandu are living proofs. It is such global gambling that has led to the recent collapse of global financial markets .. Item this time was derivatives on rates for housing mortgages .. Whatever logic of market stabilization might be advanced, underlying spirit behind derivates and futures is gambling or satta. lt is irrelevant whether it is on commodity prices, stocks, mortgage rates or exchange rates of currencies. They enable people to hedge ( or bet) on fractional changes, both up and down, in future prices. What you put at stake are minor fractions of the value of the item concerned. Consequently, millions of profit can be made in seconds on fractional 0.05% changes (termed 5 basis points when linked to interest rates in today's financial parlance). Trillions of dollars is exchanged in global trade dally.
Keywords: people; Kings; soldiers; business leaders; Lucky stars